(untitled) (Global Journal of Medical Research, 2023)
The same essential amino acids can be limiting for one kind of animals and cannot be limiting for the others which have the same ration In particular threonine is a limiting amino acid for pigs that are fed with grains but it is not limiting for human As for lysine it is a limiting amino acid for all kinds of animals 2 In the present article the reasons for limiting character of threonine and the absence of this character with reference to pigs and human are considered on the biochemical level Besides here the reasons for limiting character of one or another essential amino acid are analysed which is very important for making up ration